Portal Digital Berbasis Website dan AR/VR untuk Penguatan Link and Match melalui VocationalFive 4.0 di SMKN 5 Barru - Baso, Fadhlirrahman; Prima, Kurnia Wahyu; Nurfauziah, Nurfauziah; Jannah, Devi Miftahul; Nurjannah, Elma (Yayasan Ahmar Cendekia Indonesia, 2025)
Vocational High School (SMK) graduates in Indonesia face the problem of competency mismatch with the needs of the world of work, reflected in the high open unemployment rate of 9.42% (BPS, 2023). The community service program at SMKN 5 Barru aims to increase the capacity of teachers and students by utilizing the VocationalFive 4.0 portal based on Augmented Reality (AR) and Virtual Reality (VR). A participatory action research approach was used, including needs identification, training, mentoring, and evaluation. The results showed improved skills with an average post-test score of 85.17 and increased teacher confidence in using AR/VR. The portal was also rated as relevant for publication of work, alumni tracking, and career navigation. The findings confirm the importance of digital technology integration in vocational education, which can create interactive learning and align with industry needs. This program has the potential to become a model for developing AR/VR-based learning with an alumni tracer system.